(untitled) (Samriddhi Journal of Development Studies, 2024)
Pet owners are believed to be less lonely compared to non-owners. This study aimed to investigate the potential impact of pet ownership on mental well-being among pet owners in Kathmandu Valley. Using a quantitative research approach, data were collected through an online survey that had the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). Total of 100 participants were included. The study examined the relationship between pet ownership and mental health. The effect of other demographic variables such as age, gender, employment status, and family structure was also considered based on mean scores. Descriptive statistics and an independent sample t-test were conducted to compare well-being scores. Pet owners reported a higher mean mental well-being score (M = 47.5) than non-pet owners (M = 45.86), but the difference was not statistically significant (t(98) = 0.46, p > 0.05). Employment status and family structure appeared to have a stronger influence on mental well-being than pet ownership. Findings suggest that while pet ownership may offer minor psychological benefits, it may not determine mental well-being alone. Further research is recommended to explore the complex dynamics between pet companionship and psychological well-being in diverse socio-cultural contexts.